HEAT STRESS IN BROILERS AND THE NEED OF CLIMATIZATION SYSTEMS - dos Santos, M. P.; do Vale, M. M.; Branco, T.; Klein, D. R.; Santos, J. P. A. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Broilers have better production rates when housed in thermal comfort conditions, outside of this zone the poultry need to maintain homeothermy. The heat production and thermal exchanges are related to body weight and available surface for heat exchange. The genetic evolution of broilers ensured high production with improvement in the feed conversion and reducing the slaughter time. The faster weight gain difficult sensible heat exchange, increasing the needs for climatization systems, in days with high temperatures. Changes in heat waves frequency and days with extreme temperatures are challenging situations for ventilation and evaporative cooling systems in broiler facilities. This review discusses heat exchanges of broilers and the challenges in maintaining the thermal comfort zone in poultry facilities, in a reality of increase of heat stress conditions.